White masculinity in the death zone: transformations of colonial identities in the Himalayas - Purtschert, Patricia (Culture and religion, 2020)
The following article examines relations between masculinity and whiteness in the context of the Swiss Everest expeditions of 1952. It shows how in the mountaineering literature of the time, the so-called ‘death zone’ (beyond 8000 metres of altitude) turns into an arena for a hegemonic masculinity in crisis. This crisis encompasses ‘traditional’ elements of hegemonic Western masculinity, which is based on the abjection of the body, the emotional and the irrational. In times of decolonisation, it further comprises the collapse of imperial power and the invention of postcolonial relations between white and non-white men. As this article shows, this novel iconography of male relationality evokes images of partnership while it is still based on racial inequality.